(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2026)
Background Post-stroke hemiplegia significantly impairs gait and mobility, particularly in outpatient settings with limited access to advanced rehabilitation technologies. Neuromuscular Electrical Stimulation (NMES) may offer a feasible adjunct to conventional physiotherapy. Methods and materials This prospective case series included 20 outpatients (mean age: 51.7=/- 5.6 years; stroke onset: 6-12 months) with moderate gait dysfunction (Wisconsin Gait Scale ≥26). Participants received 4-week intervention combining NMES targeting the tibialis anterior and hamstrings with conventional physiotherapy. Gait quality and functional mobility were assessed using the Wisconsin Gait Scale (WGS) and Timed Up and Go (TUG) test respectively. Data was analyzed using Wilcoxon signed-rank tests, with 95% confidence interval reported. Results Median WGS scores improved from 24.5 to 18.97 (p< 0.001; 95% CI: 4.375-6.515), and mean TUG scores decreased from 21.05s to 17.4s (p<0.001; 95% CI: 2.483-3.487). Improvements exceeded the MCID and MDC thresholds. Qualitative gains included enhanced toe clearance, knee flexion, and increased weight- shifting on affected lower limb. No adverse events occurred. Conclusions NMES combined with conventional therapy is feasible, safe and clinically meaningful in low-resource outpatient stroke rehabilitation. These findings support further controlled trials to isolate NMES effects and evaluate long-term outcomes.